Cover Image. (20th February 2019) - Zhao, Shuangtao; Shen, Wenzhi; Du, Renle; Luo, Xiaohe; Yu, Jiangyong; Zhou, Wei; Dong, Xiaoli; Gao, Ruifang; Wang, Chaobin; Yang, Houpu; Wang, Shu
Abstract : The cover image is based on the Original Research Three inflammation‐related genes could predict risk in prognosis and metastasis of patients with breast cancer by Shuangtao Zhao et al., DOI:10.1002/cam4.1962 . Design Credit: Shuangtao Zhao.